TRANSPARENCY AND ACCOUNTABILITY IN MANAGEMENT OF VILLAGE ADMINISTRATION REVENUE AND EXPENDITURE BUDGET (APBDES) - Khotimah, Hosnol; Kustono, Alwan Sri; Martiana, Nina (Asosiasi Fakultas Ekonomi dan Bisnis Perguruan Tinggi Muhammadiyah, 2018)
After the enactment of regional autonomy, transparency and accountability have become veryimportant issues in the Regional Financial Management, including Village AdministrationFinancial Management. This research is meant to find out how far the implementation oftransparency and accountability principles of village administration in managing the VillageBudget (APBDes) at Desa Sukosari Lor, Kecamatan Sukosari, Kabupaten Bondowoso throughPlanning, Implementation, Administration, Reporting, and Accountability. The research methodused is descriptive with qualitative approach. The resource persons in this study include Headof Desa Sukosari Lor, other apparatus at Desa Sukosari Lor, Chairman and secretary of BPD(Village Consultative Board) in Sukosari Lor, Chairman of Village Community EmpowermentInstitution (LPMD), Head of Family Welfare Development (PKK) in Sukosari Lor and theresidents of Sukosari Lor as the target for various programs. Data collection techniques used arein the form of observation, interview, and documentation analysis. Data analysis is performedwith data collection, data reduction, data presentation, data testing, and making conclusion. Theresearch findings indicate that the Village Head in Desa Sukosari Lor, Kecamatan Sukosari,Kabupaten Bondowoso has implemented the principles of transparency and accountability in themanagement of 2016 budget. In general, transparency and accountability in Desa Sukosari Lor,Kecamatan Sukosari, Kabupaten Bondowoso has been running well. However, there are someproblems that still have to be fixed.